The Influence of Visionary Leadership and Teacher Pedagogical Competence on the Quality of Student Learning Outcomes at Madrasah Aliyah - Latif, Abdul; Saroni , M.; Araniri , Nuruddin (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the influence of visionary leadership and teacher pedagogical competence on the quality of student learning outcomes at Madrasah Aliyah As-Sakienah Sliyeg, Indramayu Regency. The research method uses a quantitative approach with a verification method. The research population was 115 people with a sample of 90 respondents selected using random sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 20.0. The results of the study show that: (1) visionary leadership has a positive and significant effect on the quality of student learning outcomes with a contribution of 58.76% (t-count 4.938 > t-table 1.662); (2) teacher pedagogical competence has a positive and significant effect on the quality of student learning outcomes with a contribution of 49.28% (t-count 1.971 > t-table 1.662); and (3) visionary leadership and teacher pedagogical competence simultaneously have a positive and significant effect on the quality of student learning outcomes with a contribution of 60.40% (F-count 66.354 > F-table 2.15). This study recommends the importance of strengthening the visionary leadership of madrasah principals and improving teacher pedagogical competence to improve the quality of student learning outcomes.